"The Natural Order of Creation": Naturalizing Discourses in the Christian Same-Sex Marriage Debate - Sullivan-Blum, Constance R. (Anthropologica, 2022)
Same-sex marriage is the centre of a vitriolic debate in mainline Christian denominations in the United States. Both those who advocate for same-sex marriage and those who repudiate it employ naturalizing discourses to legitimate their claims. Feminists argue that naturalizing discourses are used to authorize social power. Liberals and evangelicals vie for the power to frame the debate over same-sex marriage. LGBT Christians, on the other hand, both contribute to and resist these discourses; most claim that their sexual orientation is beyond their control, while others evoke a sense of personal agency thereby rejecting the premise of the entire debate.